Neurofeedback training for rifle shooters to improve cognitive ability - Liu, Y.; Subramaniam, S. C. H.; Sourina, O.; Shah, E.; Chua, J.; Ivanov, K. (2017 International Conference on Cyberworlds (CW), 2017)
Neurofeedback training is one type of the biofeedback training that allows the subject do self-regulation during the training according to his/her real-time brain activities recognized from Electroencephalogram (EEG) and given to him/her through visual, audio or haptic feedback. The Neurofeedback training has been proved to be helpful in improvement of cognitive abilities not only for patients with mental illnesses but also for healthy subjects including athletes. In this paper, we proposed an experiment in which we recruited elite shooters and conducted a novel individual beta-1/theta based neurofeedback training to confirm the usage of neurofeedback training in boosting the performance of rifle shooters. The efficiency of the neurofeedback training was examined by comparing the shooting scores and results of DAUF test assessing the ability of sustained attention of the shooters before and after neurofeedback training.